Gestão democrática na escola: as impressões dos participantes do programa progestão - Barreiro, Iraide Marques de Freitas [UNESP]; Moura, Gabriela Garcia (My University, 2010)
This paper is a sampling of an extensive research which analyzed and assessed the Distance Learning Program for Qualification of School Managers (Progestão) carried out in three schools, which preserved the same management team during the program. Progestão provided continuing and inservice development for public school managers by means of distance and presential types of learning. This paper deals with the concept of democratic management understood by the proponents of Progestão, the training team (trainers and multipliers), and the managers assisting the course (principals, vice principals, and pedagogical supervisors). Three issues that check the understanding of the democratic management concept were analyzed, as well as how those participants implement it in schools. The research is based on the qualitative approach, which has an evaluating character. It discusses the profile assigned to school management since the amendment of the State and the passing of the Law of Policies and Principles of Education (LDB)/96, besides pointing out the difficulties to support democratic management dissociated from other school practices.

Este artigo é recorte de uma pesquisa maior em que se analisou e avaliou o Programa de Capacitação a Distância para Gestores Escolares (Progestão) em três escolas, que mantiveram a mesma equipe gestora no decorrer do programa. O Progestão ofereceu formação continuada e em serviço aos gestores escolares da rede pública por meio de modalidades presencial e a distância. Neste artigo discute-se a concepção de gestão democrática dos proponentes do Progestão, da equipe formadora (formadores e multiplicadores) e dos gestores-cursistas (diretor, vice-diretor e supervisor pedagógico). Foram analisadas três questões que aferem a compreensão do conceito gestão democrática e como os partícipes do programa o implementaram na escola. A pesquisa fundamenta-se na abordagem qualitativa, de cunho avaliativo. Discute o perfil atribuído à gestão escolar a partir da reforma do Estado e da aprovação da Leia de Diretrizes e Bases da Educação Nacional - LDB/96, além de apontar as dificuldades em se promover a gestão democrática dissociada das demais práticas escolares.
Democratic management in schools: impressions conveyed by participants of the program pro management
Keywords: Management; Democratic management; Continuing development; Public policies; Gestão; Gestão democrática; Formação continuada; Políticas públicas